Neural Correlates of Sequence Encoding in Visuomotor Learning - Agam, Yigal (American Physiological Society, 2010)
To examine the neural basis of sequence learning, a fundamental but poorly understood human ability, we recorded event-related potentials (ERPs) while subjects viewed and memorized randomly directed sequences of motions for later imitation. Previously, we found that the amplitude of ERPs elicited by successive motion segments decreased as a function of each segment's serial position. This happened when subjects were required to remember the sequence, but not when they were performing a perceptual task. Here, to study the functional significance of this amplitude gradient in sequence learning, we presented each sequence several times in succession and examined changes in ERP amplitude as subjects learned the sequence through repeated observation and imitation. Behaviorally, with each repetition subjects grew more accurate in reproducing what they had seen. At the same time, ERPs grew smaller with each successive presentation, replicating and extending previous demonstrations of repetition suppression. Importantly, a comparison of ERPs to segments occupying different serial positions within a sequence revealed a decreasing amplitude gradient that grew steeper with sequence repetition. This sharpening of the amplitude gradient may reflect an explicit encoding process that relies on a magnitude code for serial order.